A BIBLIOMETRIC ANALYSIS OF AWE IN ACADEMIC WRITING: INSIGHT FROM THE SCOPUS DATABASE - Hana Nur Hanifah; Muhamad Taufik Hidayat; Wahid Hasim (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study investigates the development and research trends of Automated Writing Evaluation (AWE) in academic writing through a bibliometric approach. A total of 75 documents were retrieved from the Scopus database, covering publications between 2015 and 2025, and were analyzed using VOSviewer. The analysis focused on three dimensions: (1) publication trend analysis to chart the growth of AWE scholarship over time; (2) keyword co-occurrence analysis to identify dominant concepts and thematic clusters; and (3) thematic mapping to reveal emerging research directions and future opportunities. The findings reveal a marked upward trend in AWE research output, with publication volume remaining modest between 2015 and 2021 before rising sharply from 2022 onward, culminating in 22 documents in 2025 alone. Keyword analysis identified